The early proterozoic Makganyene glacial event in South Africa : its implication in sequence stratigraphy interpretations, paleoenvironmental conditions and iron and manganese ore deposition - Polteau, Stéphane (Rhodes University, Faculty of Science, Department of Geology, 2005)
The Makganyene Formation forms the base of the Postmasburg Group in the Transvaal Supergroup in the Griqualand West Basin. It consists of diamictites, sandstones, banded iron-formations (BIFs), shales, siltstones and carbonates. It is generally accepted that the Makganyene Formation rests on an erosive regional unconformity throughout the Northern Cape Province. However this study demonstrates that this stratigraphic relationship is not universal, and conformable contacts have been observed. One of the principal aims of this study is to identify the nature of the Makganyene basal contact throughout the Griqualand West Basin. Intensive fieldwork was carried out from Prieska in the south, to Danielskuil in the north. In the Sishen and Hotazel areas, only borehole material was available to assess the stratigraphy. The Griquatown Fault Zone delimits the boundary between the deep basin and platform facies. The Koegas Subgroup is only present south of the Griquatown Fault Zone, where it pinches out. However, the transition Griquatown BIFs-Koegas Subgroup occurs in lacustrine deposits on the Ghaap platform (Beukes, 1983). The Griquatown Fault Zone represents the edge of the basin, which corresponds to a hinge rather than a fault zone. The Makganyene Formation rests with a conformable contact on the Koegas Subgroup south of the Griquatown Hinge Zone, and north of it the Makganyene Formation lies unconformably on the Asbestos Hills Subgroup. The Makganyene Formation displays lateral facies changes that reflect the paleogeography of the Griqualand West Basin, and the development of ice sheets/shelves. The Ghaap platform is characterised by coarse immature sand interbedded with the diamictites. The clasts in this area contain local Asbestos Hills material and no dropstones are present. Such settings are typical of sediments that are being deposited below a grounded ice mass. At the Griquatown Hinge Zone, the sandstone lenses are smaller, and the clasts consist of chert, of which a great number are striated and faceted. In the Matsap area, the presence of dropstones is strong evidence for the presence of a floating ice shelf that released its material by basal melting. Further south, the Makganyene Formation contains stromatolitic bioherms that only form if clastic contamination is minimal and therefore the ice that transported the detritus to the basin did not extend far into open sea conditions. The base of the Hotazel Formation also contains diamictite levels. Dropstones have been identified, implying a glacial origin. The Hotazel diamictites are interbedded with hyaloclastites and BIFs. The Makganyene glacial event, therefore, was not restricted to the Makganyene Formation, but also included the Ongeluk Formation, through to the base of the Hotazel Formation. Petrographic studies of the Makganyene Formation and the base of the Hotazel Formation reveal mineral assemblages that are diagnostic of early to late diagenetic crystallisation and of low-grade metamorphism not exceeding the very low green-schist facies. The facies identified display the same sense of basin deepening, from shallow high-energy Hotazel area on the Ghaap platform, to the deep basin in the Matsap area. Whole-rock geochemical analyses reveal that the elemental composition of the Makganyene Formation is very similar to that of the Asbestos Hills BIFs, which were the most important source of clastic detritus for the Makganyene Formation. However, minor amounts of carbonates of the Campbellrand Subgroup, as well as a felsic crustal input from the Archean granitoid basement, made contributions. On the Ghaap platform, the Makganyene diamictite is enriched in iron, calcium, and magnesium, while in the deeper parts of the basin the diamictites are enriched in detrital elements, such as titanium and aluminium, which occur in the fine clay component. The Hotazel diamictite displays a distinct mafic volcanic input, related to the extrusion of the Ongeluk basaltic andesites, which was incorporated in the glacial sediments. Sequence stratigraphy is based on the recognition of contacts separating the different systems tracts that compose a depositional sequence. However, because the basal contact of the Makganyene Formation has not been properly identified in previous work, no correct model has been proposed so far. Therefore correlations between the Griqualand West and the Transvaal basins, based on lithostratigraphic similarities and extrapolations of unconformities, have to be reviewed, especially since the publication of new radiometric ages contradict all previously proposed correlations. It is proposed here that the Transvaal Supergroup in the Griqualand West Basin represents a continuous depositional event that lasted about 200 Ma. The Makganyene glacial event occurred during changing conditions in the chemistries of the atmosphere and ocean, and in the continental configuration. A Snowball Earth event has been proposed as the causative process of such paleoenvironmental changes. However, evidence presented here of less dramatic glacial conditions, with areas of ice-free waters, implies an alternative to the Snowball Earth event. The paleoenvironmental changes are thought to represent a transition from an anaerobic to aerobic atmosphere, that was responsible for the global cooling of the surface of the Earth, Such a glacial event may have aided in the large-scale precipitation of iron and manganese in areas of intense upwellings.
Keywords: Geology, Stratigraphic -- South Africa -- Northern Cape; Geochemistry -- South Africa -- Northern Cape; Paleogeography -- South Africa -- Northern Cape; Petrology -- South Africa -- Northern Cape; Ore deposits -- South Africa -- Northern Cape